Shalat Jama’ Mempelai Wanita Menurut Hukum Islam (Studi Kasus di Desa Kuranji, Kecamatan Kuranji Kota Padang) - Amri Effendi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
The focus of the study in this article is the law of jamming prayers for the bride at the wedding. Jama' prayers are basically permitted by Islamic teachings, to provide convenience if there are obstacles that are syar'i in nature, but what about the case with a wedding party, is it a syar'i obstacle, and what is the view of Islamic law towards the bride and groom who jama' prayers on the day of the party? marriage. In discussing this issue, the authors use qualitative methods using a "case study" approach. In collecting data, the writer used interview, observation, and literature search techniques. The data is processed and analyzed qualitatively using descriptive analysis by explaining and interpreting it rationally, objectively and consistently. With the finding that the jama' prayer is only permissible at times of travellers, heavy rain, illness, fear, and very urgent conditions, but for brides who perform the jama' prayer during the wedding, no information is found in the texts, so this practice have not been able to enter in the case that is justified